Microplastic contamination in the Yucatan Peninsula karst aquifer - Mendoza-Olea, Itzel Jocelin; Leal-Bautista, Rosa María; Cejudo, Eduardo; Cervantes-Uc, José Manuel; Rodríguez-Fuentes, Nayeli; Acosta-González, Gilberto (Ecosistemas y Recursos Agropecuarios, 2022)
Microplastics (PM) pollution affects terrestrial, aquatic and aerial ecosystems. There are few studies that have analyzed the presence of PM in groundwater. The Yucatan Peninsula Karst Aquifer (AKPY) is the region’s main source of water supply. Therefore, the objective of this study was to determine the presence of MP in AKPY. Water samples were taken from cenotes and wells, filtered and the material retained in the filter was observed under a stereoscopic microscope to identify and classify PM. The PM forms observed were fibers (94%) and the most abundant color was white (51%). The maximum concentration was 936 particles L−1 and the minimum 10 particles L−1. PM was found in all groundwater samples, so determining sources is critical to mitigating its presence in AKPY.